The Influence of Exports and Investment on GRDP in North Sumatra, 2001 – 2020 - Juan Charlos Sibarani; Arnol Prabowo Siagian; Ros Juliana Lubis; Hasyim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to examine the influence of export and investment on GRDP in North Sumatra from 2001 to 2020. Data in the research is obtained from BPS, which is secondary data with the method of data collection, documentation and study books, data analysis technique performed with linear regression analysis and testing. hypothesis partial then simultan serta melihat nilai coefficient determinasi. Hasil peresikaan sampaan sakada sluhan ekpor dan investasa secraa siginifan tapatan utwats GRDP. Although export can produce a large income for the country, it depends on the condition of the global market and the availability of resources in the country. Dampak ekspor dan investasa tepadan GRDP juga dapat oleh oleh factor lain, seperti fiscal policy dan monetare, level inflation, dan stability politik.